Molecular Biomarkers of Glioma - Punsasi Rajakaruna; Stella Rios; Hana Elnahas; Ashley Villanueva; David Uribe; Sophia Leslie; Walaa A. Abbas; Larissa Barroso; Stephanie Oyervides; Michael Persans; Wendy Innis-Whitehouse; Megan Keniry (Biomedicines, 2025)
In this review, we discuss how mutations in glioma are associated with prognosis and treatment efficacy. A fascinating characteristic of glioma and all cancers is that while common growth and developmental pathways are altered, the characteristic mutations are distinct depending on the specific type of tumor with concomitant prognoses. Next-generation sequencing, precision medicine, and artificial intelligence are boosting the employment of molecular biomarkers in cancer diagnosis and treatment. Understanding the biological underpinnings of distinct mutations on critical signaling pathways is crucial for developing novel therapies for glioma.